Synthesis of bay-linked perylene dimers with enhanced solubility for high optical density black matrix material. (December 2019) - Yuk, Sim Bum; Lee, Jae Moon; Namgoong, Jin Woong; Sakong, Chun; Hwang, Tae Gyu; Kim, Se Hun; Lee, Woosung; Kim, Jae Pil
Abstract: Perylene diimides (PDIs) have been used in various industries, especially in devices such as organic light-emitting diodes, organic semiconductors, and thin-layer organic photovoltaics, because of their excellent optical and electrical properties and outstanding thermal stability. In addition, PDIs are suitable for black matrix and black bank materials, which require wide and strong absorption of visible light, for use in display panels. Research has been conducted to apply solution-processed PDI on the black matrix and black bank film fabrication. However, due to the low solubility of PDI, industrially required optical properties have not been achieved. In this study, diphenyl-linked PDI dimers were synthesized and evaluated on their optical properties and thermal stability for solution-processed black matrix. The solubility of the synthesized dimers was improved compared to that of monomers as intermolecular interaction reduced by two PDI cores in a molecule that is rotated at a specific angle. Five kinds of dimeric and monomeric PDIs were synthesized with bay substituents of different electron donating power. The absorption range of the dyes was red-shifted as the electron donating power of the substituents increased, and the fluorescence of the dyes was quenched by intramolecular charge transfer (ICT). In a solution state, dimers showed enhanced absorbance and thermal stability and enlarged absorption range as compared to the monomers. Hybrid-type black matrices using dimeric PDIs and carbon black showed high thermal stability, flat surface condition, and low dielectric constant. Additionally, the optical density of the black matrices, which was not satisfactory in the previous study, was greatly improved (up to 2.755) because of the increased dye content due to highly soluble dimeric PDIs. Graphical abstract: Image 1 Highlights: Highly soluble dimeric perylene dyes were synthesized and used as colorant of black matrix. The optical and physical properties of the dimers were measured in comparison with the monomers. A higher optical density was obtained than the previous studies due to enhanced solubility of the dyes.